Developing intercultural communicative competence in ELF communication - Cavalheiro, Lili (ELOPE (Ljubljana), 2015)
The traditional notion of English as a foreign language solely for communicating with native speakers can no longer be applied in a world that is constantly changing, hence paving the way for an alternative use of the language known as English as a lingua franca. As a result, instead of focusing only on grammatical correctness, research into language pedagogy has also come to recognize the importance of exploring bottom-up learning processes, and developing intercultural communicative competence (ICC) and more communicative-based methods. Nowadays, it is essential to acquire the knowledge, skills, attitudes and critical cultural awareness necessary to communicate successfully. To show the importance of integrating ICC in language pedagogy, a recording from the Vienna-Oxford International Corpus of English is analysed here to demonstrate the significance of developing critical awareness as well as several communicative strategies, so that language learners can afterwards have the necessary ICC to interact in today's multi-lingual/cultural society.
Keywords: angleščina kot tuji jezik; komunikacijske strategije; medkulturna komunikacijska kompetenca; tuji jeziki